PENINGKATAN PRODUKTIVITAS DAN PENDAPATAN USAHATANI PADI MELALUI SISTEM TANAM JAJAR LEGOWO DI KECAMATAN SEDAYU BANTUL - Winarno, Kodrad (Politeknik Pembangunan Pertanian Yogyakarta-Magelang, 2018)
The Government of Indonesia (GOI) has been developing agricultural sector to double the production of rice as the main staple food. By intensifying paddy production through jajar legowo planting system, the GOI has been able to increase paddy production and farmers welfare. This study was conducted in Sedayu Sub District from August to October 2017. The aims of this study were 1) to identify the productivity of paddy tegel planting system and paddy jajar legowo (2:1) planting system; and 2) to determine farmers income of paddy tegel planting system and paddy jajar legowo (2:1) planting system. This study implemented descriptive quantitative research. The participants were selected through purposive sampling. The participants were drawn from the population of Argorejo Farmer Group Association (Gapoktan) in Sedayu Sub District. The results show that the productivity of paddy jajar legowo (2:1) planting system was higher (9,04 tonnes/ha) compared to paddy tegel planting system (7,74 tonnes/ha). In addition, farmers net-income from paddy jajar legowo (2:1) planting system was also higher (Rp 30.012.395,83/ha) than paddy tegel planting system (Rp 22.400.344,05/ha). The results of this study can be used to convince farmers in employing the paddy jajar legowo (2:1) planting system rather than the tegel planting system.